Intolerance, Religious Lynchings and the Future of Indonesia - Andre Vltchek (Japan Focus)
Twice in the same week two gruesome attacks shook Indonesia and the world. On February 6, 2011, in Cikeusik Village, West Java – more than 1.000 furious Muslims lynched three members of a minority (or, as seen by some Muslims, ‘deviant’) Islamic sect Ahmadiyah. Two days later, on February 8 in Temanggung, Central Java, a crowd stormed a local courthouse and vandalized three churches after a man – a former priest who allegedly insulted both Islam and Christianity in his pamphlet – was sentenced to five years in prison, the maximum sentence. Protesters demanded the death penalty. A third attack soon followed.